2022
DOI: 10.1002/anie.202213855
|View full text |Cite
|
Sign up to set email alerts
|

Mutability‐Landscape‐Guided Engineering of l‐Threonine Aldolase Revealing the Prelog Rule in Mediating Diastereoselectivity of C−C Bond Formation

Abstract: l‐threonine aldolase (LTA) catalyzes C−C bond synthesis with moderate diastereoselectivity. In this study, with LTA from Cellulosilyticum sp (CpLTA) as an object, a mutability landscape was first constructed by performing saturation mutagenesis at substrate access tunnel amino acids. The combinatorial active‐site saturation test/iterative saturation mutation (CAST/ISM) strategy was then used to tune diastereoselectivity. As a result, the diastereoselectivity of mutant H305L/Y8H/V143R was improved from 37.2 %sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…We further compared the diastereoselective mechanisms of Nm LTA with two other LTAs, namely, Cp LTA ( Cellulosilyticum sp) and Pp LTA . Notably, Cp LTA has been previously found to contain two different substrate binding channels that govern the enzyme diastereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We further compared the diastereoselective mechanisms of Nm LTA with two other LTAs, namely, Cp LTA ( Cellulosilyticum sp) and Pp LTA . Notably, Cp LTA has been previously found to contain two different substrate binding channels that govern the enzyme diastereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, Nm LTA exhibited the highest de value of 89.5% and an efficient enzymatic activity (64.8 U mg –1 ) that was ∼1.4-fold higher than the highest native LTA reported so far (Figure B and Table ). Furthermore, only one pair of diastereomeric products, l - threo -MTPS and l - erythro -MTPS, were detected in the aldol reaction catalyzed by Nm LTA (Figure S2). Further analyses showed that Nm LTA had a maximum enzymatic activity at 30 °C and pH 8.0, and the efficiency could be further improved by increasing the PLP concentration (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational design based on calculation of binding energy was also applied to design enzyme variants with improved diastereoselectivity. It was assumed that for the L-threonine aldolase (LTA) from Bacillus nealsonii ( Bn LTA), the syn -configuration was formed by substrate 4-methylsulfonyl benzaldehyde (MTB) attack of the α-carbon atom of pyridoxal phosphate (PLP)−glycine through the syn path, and the anti -configuration was formed by attack of the α-carbon atom of PLP−glycine through the anti path ( Zheng et al, 2020 ; Zheng et al, 2023 ). Hence, in order to improve diastereoselectivity of Bn LTA towards syn -configuration product, the variants in syn -path with improved binding affinity to substrate and the variants in anti -path with reduced binding affinity to substrate were virtually screened by calculating binding energy using tool of Discovery Studio.…”
Section: Computational Protein Designmentioning
confidence: 99%